ISKANDAR MIRZO IS A DEFENDER OF CULTURE AND THE ART (Scientific journal of the Fergana State University, 2023)
The article examines the involvement and sponsorship of the Temurid prince Iskandar in cultural life. Uzbek and foreign researchers have studied the activities of Iskandar Mirzo and analysed the written sources that serve to study this issue. Factors influencing the development of science, literature, art and formation of cultural environment in the cities of Sheraz and Isfahan under the patronage of the prince are based on historical sources. Furthermore, the role of Iskandar Mirzo in the development of cultural life in the Temurid period is emphasized.